(3JMaI Gdedhc hGdQZGFH deG aj GdHQ hGdHMQ ef GdYLGFH hGdZQGFHs - (3fhQ GdOjf CMeO Hf Ydj Hf CMeO GdeMdi GdTGaYj GdeYQha HGHf RfHd GdQeGd,J (B980 (3g` s ((3Rjf GdOjf GdWQGHdSi s)
(3ChdgG (B:s
(3GdMeO ddg HGSW GdCQV Hjf GdeGA hGdghi GdPi NdbgG hGdSehGJ ai SJI CjGe hYdi GdYQT ESJhi CPcQ ajg cKjQkG eeG JQcJg ai GdChd hCUhQ ajg eG JjSQ ef EXgGQ GdCQV hLHGdgG s
(3BNQgG (B:s
(3hdG KHJ TF ef GdehLhOGJ Ydi GdMGd GdCaVd aGYde Pdc CjgG GdCN hJacQ ajg aEfg Yde jgOi Edi ShGA GdUQGW hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs